The Effect of Teaching Creativity, Classroom Management Ability, and Life Skill Education on the Implementation of Child Friendly Schools - Aji, Ewati Munawaroh; Suminar, Tri; Nuswowati, Murbangun (Educational Management, 2021)
Schools must be a safe place for students. Teachers, students and school members must understand child protection regulations. Violence, bullying or other negative actions should not be carried out against students. Education implemented by schools must be humanist education. It takes teachers who are creative in teaching and able to manage the class well and are able to internalize life skill education for students through exemplary, invitation and teacher motivation. This study aims to analyze the effect of teaching creativity, the ability to manage classes, and life skills education on the implementation of child-friendly schools.The research design used ex post facto correlational research. The data analysis technique used regression analysis. The study population was public and private elementary schools class teachers in Semarang City. The research sample consisted of 49 teachers using purposive sampling technique. The data collection technique used unstructured interviews, questionnaires, and documentation. The results showed that teaching creativity had a significant effect of 30.4% on the implementation of child-friendly schools, the ability to manage classes had a positive and significant effect of 32.7% on the implementation of child-friendly schools, life skills education has a positive and significant effect on the implementation of child-friendly schools by 26.6%.